GENE EXPRESSION ANALYSIS: INDICATORS OF NITROGEN USE EFFICIENCY IN POTATO CULTIVARS - Tiwari, Jagesh K; Trehan, S P; S, Sundaresha; Poonam, Poonam; Singh, B P; Dua, V K; Bhardwaj, Vinay (Potato Journal, 2015)
Â Â